Managing self-explaining ambient applications - Kordts, Börge; Brandl, Lea C.; Schrader, Andreas (Frontiers in the Internet of Things, 2025)
IntroductionThe Internet of Things (IoT) plays a crucial role in realizing the vision of pervasivemcomputing. The variety of devices and services in the IoT often makes manual integration complex and tedious. To mitigate this challenge, self-organization has emerged as a promising approach. Furthermore, the concept of selfexplainability has been proposed to clarify user interactions with dynamically interconnected smart objects.MethodsThis paper explores related research in the domains of (a) service composition, (b) self-explainability, and (c) application management within smart environments. To address existing limitations, we propose a novel application management concept. Therefore, we extended a framework that utilizes self-explaining applications to generate user instructions dynamically that explain the control of these. A user study was conducted to assess the effectiveness and preferred options of modalities of these instructions.ResultsThe findings indicate that the approach successfully tackles the research question concerning the integration of self-explaining applications into smart environments.